Ernst Rüdin's Unpublished 1922-1925 Study "Inheritance of Manic-Depressive Insanity": Genetic Research Findings Subordinated to Eugenic Ideology. - Gundula Kösters; Holger Steinberg; Kenneth Clifford Kirkby; Hubertus Himmerich (PLoS Genetics)
In the early 20th century, there were few therapeutic options for mental illness and asylum numbers were rising. This pessimistic outlook favoured the rise of the eugenics movement. Heredity was assumed to be the principal cause of mental illness. Politicians, scientists and clinicians in North America and Europe called for compulsory sterilisation of the mentally ill. Psychiatric genetic research aimed to prove a Mendelian mode of inheritance as a scientific justification for these measures. Ernst Rüdin's seminal 1916 epidemiological study on inheritance of dementia praecox featured large, systematically ascertained samples and statistical analyses. Rüdin's 1922-1925 study on the inheritance of "manic-depressive insanity" was completed in manuscript form, but never published. It failed to prove a pattern of Mendelian inheritance, counter to the tenets of eugenics of which Rüdin was a prominent proponent. It appears he withheld the study from publication, unable to reconcile this contradiction, thus subordinating his carefully derived scientific findings to his ideological preoccupations. Instead, Rüdin continued to promote prevention of assumed hereditary mental illnesses by prohibition of marriage or sterilisation and was influential in the introduction by the National Socialist regime of the 1933 "Law for the Prevention of Hereditarily Diseased Offspring" (Gesetz zur Verhütung erbkranken Nachwuchses).